A ativação do adrenoceptor-β2 pelo formoterol induz a exocitose cálcio-dependente de vesículas sinápticas na junção neuromuscular de camundongos - Kivia Barretos Soares Santos (2022)
The noradrenergic system has a wide range of effects in different physiological systems and the effects on skeletal muscle mainly occur via the activation of β-family receptors. In the skeletal muscle, the β2 receptors are the most abundant and their activation promotes several signaling pathways that result in anabolic processes and hypertrophy. The use of β2-adrenergic agonists in skeletal muscle has been considered a potential drug for treatment of pathologies that can generate muscle atrophy. Meanwhile, its effect on the neuromuscular junction and on the cholinergic synapses are still poorly explored. Thus, the objective of this work is to evaluate the presynaptic effects of the specific β2-agonist drug formoterol fumarate on neuromuscular synaptic transmission in mice diaphragm ex-vivo preparations. For this study, the diaphragm muscles associated with the phrenic nerve from three-month-old male and female C57 mice were isolated. Synaptic vesicles exocytosis at the neuromuscular pre- synaptic terminals was visualized and monitored with the use of the vital dye FM1-43 and fluorescence microscopy. After stained preparations were incubated with formoterol fumarate at increasing concentrations (0.01, 0.1, 0.25, 1, 10 e 50 μM) in order to build a dose-response curve. Our results show that formoterol evokes exocytosis of synaptic vesicles in the diaphragmatic neuromuscular junctions in both male and female animals. Formoterol presented a considerable effect in the concentration of 0.1 μM, with a fluorescence decay of approximately 40% in males. The rate of decay of the fluorescent signal which reflects exocytic activity is directly proportional to the increase of the drug concentration in males. Females appear to be less sensitive to the effects of formoterol since in all concentrations the effect observed was similar. These results suggest that formoterol evokes the exocytosis of synaptic vesicles at neuromuscular junctions. To go deeper into the mechanisms by which formoterol can evoke synaptic vesicles exocytosis, we co-stimulated the preparations with formoterol plus KCl, a sodium-independent exocytosis-inducing compound. We observed an additive effect of KCl and formoterol, given that the rate of decay of the fluorescent signal increased as the concentration of formoterol increased. Therefore, we hypothesized that formoterol and KCl induced exocytosis through different mechanism. This study demonstrates that formoterol has presynaptic actions and increases both spontaneous and evoked exocytosis. The results obtained may pave the way for future studies that will elucidate the mechanisms of action of β2 agonists in skeletal muscle and consolidate this class of drugs as a therapeutic strategy for the treatment of myasthenia and several other neuromuscular pathologies.